1995
DOI: 10.1128/jb.177.20.6018-6020.1995
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenase does not confer significant benefits to Azotobacter vinelandii growing diazotrophically under conditions of glucose limitation

Abstract: The presumed beneficial effect of hydrogenase on growth of diazotrophic bacteria was reinvestigated with carbon-limited chemostat cultures of the hydrogenase-deficient mutant hoxKG of Azotobacter vinelandii and its parent. The results revealed that hydrogen recycling was too low to benefit the cellular energy metabolism or activities of nitrogenase and respiration.Reduction of dinitrogen to ammonia by nitrogenase is accompanied by the production of hydrogen (17). Since organisms which express an uptake hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In diazotrophic organisms and particularly in aerobic azotobacters, the high energy requirement of nitrogenase contributes significantly to the high maintenance activities known for these organisms (16,29). It was reported before that increases in the dissolved oxygen concentration were accompanied by increases in the maintenance requirements of diazotrophic cultures of A. vinelandii and decreases in the Y values (14,17). Importantly, however, it was also reported that the true growth yield (Y G ) remained constant in cultures grown at different dissolved oxygen concentrations and carbon sources.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In diazotrophic organisms and particularly in aerobic azotobacters, the high energy requirement of nitrogenase contributes significantly to the high maintenance activities known for these organisms (16,29). It was reported before that increases in the dissolved oxygen concentration were accompanied by increases in the maintenance requirements of diazotrophic cultures of A. vinelandii and decreases in the Y values (14,17). Importantly, however, it was also reported that the true growth yield (Y G ) remained constant in cultures grown at different dissolved oxygen concentrations and carbon sources.…”
Section: Discussionmentioning
confidence: 93%
“…Since diazotrophic cultures can be considered energy limited and since the concentration of the energy source in the feed (S R ) was constant, it follows that the observed D-dependent increases in the steady-state levels of both S (ATP) and X were due to an increase in the efficiency of energy utilization (Y ATP ) for biomass formation, i.e., dinitrogen fixation. Augmentation of Y may be explained by the fact that, upon increasing the substrate supply with increasing D, the relative influence of maintenance functions on Y decreases (17,22). In diazotrophic cultures of A. vinelandii, the unusually high maintenance activities with glucose and other carbon sources vary largely in direct proportion to the oxygen concentration (14,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations